The effect of flipped classroom based on team games tournament on mathematics problem-solving ability - Dianty, Robbyah Muhyi; Yurniwati, Yurniwati; Lestari, Ika; Manahor, Anwar (Research and Social Study Institute, 2023)
The study aimed to determine the effect of flipped classroom modified Teams Games Tournament (TGT) on mathematics problem-solving skills in terms of self-regulated learning in students. This research is a type of quantitative research with the quasi-experimental method. The population in this study came from Krunjo State Elementary School, Tangerang Regency. The research sample came from two classes, namely class III A (experimental class) and class III B (control class), totaling 46 students. The sampling technique was cluster sampling. Data analysis is quantitative statistical analysis with the Two Way Anova test with the help of the JAMOVI application. The results of this study showed: 1) there is an effect of flipped classroom learning modified Team Games Tournament (TGT) on students' math problem-solving can be seen from the results of Two Way Anova p-value < α, namely the value of 0. 006 < 0.05; 2) There is a significant interaction between students who learn with flipped classroom modified Team Games Tournament (TGT) on students' mathematical problem-solving ability can be seen from the p-value < α, namely the value of 0.045 < 0.05. 3) There is a difference between students who learn with flipped classroom modified Team Games Tournament (TGT) in terms of high self-regulated learning can be seen from the value of p- tukey> α or 0. 023 < 0.05.